Understanding and Perception of Electronic Medical Record Systems among Health Science Cluster Students: A Systematic Literature Review - Danang Wahansa Sugiarto; Ayudhia Rachmawati (Media Publikasi Promosi Kesehatan Indonesia (MPPKI), 2025)
Introduction: As technology has developed, many countries have mandated the implementation of electronic medical records. The introduction and understanding of electronic medical records should begin at the lecture stage, especially in the health science studies (health science cluster). This study aims to assess the understanding and perception of students in the health science cluster regarding electronic medical records. Methods: This study uses a systematic literature review protocol based on the Preferred Reporting Items for Systematic Review and Meta-Analyses (PRISMA). A literature search in three databases, PubMed, Sage Journal, and Science Direct, yielded 75 article findings. After the review process, 8 eligible articles were selected based on the inclusion and exclusion criteria. Results: From the 8 selected research articles, it was found that students' understanding, perceptions, and experiences related to electronic medical records were very positive. The analysis revealed that electronic medical records can significantly enhance collaboration between medical personnel and healthcare workers, improve professional career development, and raise the quality of health services. Conclusion: The acceptance and perception of students in the health science cluster are positive regarding electronic medical record learning materials. They feel very helped by the existence of electronic medical records because it makes their work easier and efficient, and also adds skills in the application of information technology in the health sector. In the future, electronic medical record learning can be developed across all disciplines in the health science cluster, such as in the health information technology module. In addition, the subject matter in learning related to the ethics of managing electronic medical records can be further developed.